2019
DOI: 10.1002/14651858.cd013334
|View full text |Cite
|
Sign up to set email alerts
|

Low carbohydrate versus balanced carbohydrate diets for reducing weight and cardiovascular risk

Abstract: Low carbohydrate versus balanced carbohydrate diets for reducing weight and cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Thus, measures must be taken to address these issues, such as promoting healthy eating habits and increasing physical activity. Public health campaigns and initiatives can play a crucial role in educating people about the importance of a balanced diet and an active lifestyle [ 13 ]. Policymakers can also implement measures such as food labeling and taxation on unhealthy foods to encourage healthier choices.…”
Section: Introduction To the Western Dietmentioning
confidence: 99%
“…Thus, measures must be taken to address these issues, such as promoting healthy eating habits and increasing physical activity. Public health campaigns and initiatives can play a crucial role in educating people about the importance of a balanced diet and an active lifestyle [ 13 ]. Policymakers can also implement measures such as food labeling and taxation on unhealthy foods to encourage healthier choices.…”
Section: Introduction To the Western Dietmentioning
confidence: 99%
“…KD —diets with minimal carbohydrate intake, moderate protein intake and increased fat intake [ 111 , 112 ]. The dynamics of publications on this topic from 2015 to 2021 are shown in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al previously reported an increased incidence of AF in humans with lower carbohydrate intake over a median follow-up of 22 years [41]. However, it remains unclear if the risk of AF, varying with carbohydrate intake levels, shows significant differences in the short term, such as within a 5-year follow-up period [42]. Moreover, in the current study, the carbohydrate contributes to 44% of the total calories of HPD, which is close to the Institute of Medicine's carbohydrate standard, constituting 45-65% of total caloric intake [43].…”
Section: Discussionmentioning
confidence: 99%